2018
DOI: 10.1590/s1678-86212018000300285
|View full text |Cite
|
Sign up to set email alerts
|

Ventilated cladding systems: structural and drainability performance criteria

Abstract: Abstractladding systems have significant effect on the performance and durability of building façades, contributing to the building watertightness, property valuation, aesthetic finishing, and decoration. Non-adherent cladding, also named rainscreen cladding or ventilated cladding, is currently used in residential and commercial buildings, new constructions, or retrofit operations, and it is considered an efficient measure to improve the moisture safety of building envelopes. Therefore, the absence of Brazilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
1
Order By: Relevance
“…Few studies related to the performance of ventilated façade have shown a reduction of 20-40% of cooling energy demand. However, this reduction is correlated to parameters as thermal performance of the layers, insulation status of the inner façade, the height and the width of the air cavity, the type of ventilation, the climatic context, solar exposure, and wind status [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies related to the performance of ventilated façade have shown a reduction of 20-40% of cooling energy demand. However, this reduction is correlated to parameters as thermal performance of the layers, insulation status of the inner façade, the height and the width of the air cavity, the type of ventilation, the climatic context, solar exposure, and wind status [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Por meio destes instrumentos foi possível entender detalhadamente as ações desenvolvidas e as dificuldades vivenciadas para implementar a NBR 15575:2013. GARLET et al, 2017;SILVA, 2017;MUNIZ-GÄAL et al, 2018;SILVA et al, 2018;TUBELO et al, 2018;DALBEM et al, 2019Desempenho Acústico RIBEIRO et al, 2014SCHVARSTZHAUPT;NUNES, 2014;ZANNIN, 2016;GARLET et al, 2017;PACHECO et al, 2017;SANTANA et al, 2017;KLIPPEL FILHO et al, 2018;SILVA et al, 2018Resistência ao fogo BOLINA et al, 2015BOLINA et al, 2017;HENNEMANN et al, 2017;KLIPPEL FILHO et al, 2018 Entre os documentos analisados destacaram-se padrões e registros dos sistemas de gestão da qualidade, checklists de projetos de arquitetura e engenharia e resultados de ensaios e simulações realizadas pelas empresas. Os dados obtidos foram compilados, triangulados e analisados criticamente de forma a caracterizar e permitir a avaliação da implementação da norma de desempenho.…”
Section: Gestão and Tecnologia De Projetosunclassified
“…The façade is one of the basic elements used to enhance a building, although its functions are broader than just the aesthetics of the building. Cladding systems have a significant effect on the performance and durability of façades, contributing to watertightness, real estate value, and aesthetic finishing 1 …”
Section: Introductionmentioning
confidence: 99%
“…Ventilated façade systems are considered as a sustainable solution for building façades due to its aesthetic and energy efficient characteristics 2 1,3,4 . Currently, different coating materials can be used, including fiber cement panels, composite aluminum, natural stone slabs such as marble and granite, metal slabs, and porcelain tiles 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation